(untitled) (Rupandehi Campus Journal, 2024)
This study presents a critical analysis of five legal precedents established by the Supreme Court of Nepal involving medical negligence, with the aim of understanding the legal principles, challenges, and implications in such cases. The primary objective of this research is to contribute to the discourse on patient rights, doctor accountability, and healthcare quality. To achieve this, a case law study approach was adopted, involving critical analysis of relevant case law. The selected precedents were thoroughly examined to identify legal principles, judicial reasoning, and the application of laws in different contexts related to medical negligence. The key findings from the analysis of the case laws emphasize the importance of ethical conduct and professionalism in medical practice, the judiciary’s commitment to upholding justice, and the balance between patient rights and doctors’ accountability through the distinction between civil and criminal liability.